Antimicrobial use and its association with the presence of methicillin-resistant staphylococci (MRS) and extended-spectrum beta-lactamases (ESBL)-producing coliforms in mastitic milk on dairy farms in the Chiba Prefecture, Japan. Issue 12 (December 2022) - Kikuchi, Masato; Okabe, Takuma; Shimizu, Hideshige; Matsui, Takashi; Matsuda, Fuko; Haga, Takeshi; Fujimoto, Kyoko; Endo, Yuko; Sugiura, Katsuaki
Abstract: Food-producing animals, including dairy cattle, are potential reservoirs of antimicrobial resistance. However, there is limited data on antimicrobial use and the selection of resistant bacteria. Therefore, we investigated the association between antimicrobial use and resistance to mastitis pathogens using 2016 data from milk samples collected from cows with mastitis in 134 dairy farms in Chiba Prefecture, one of the principal dairy production prefectures in Japan. We recorded the antimicrobial use and isolation of methicillin-resistant staphylococci (MRS) and extended-spectrum beta-lactamase (ESBL)-producing coliforms ( E. coli and Klebsiella spp.), and used the antimicrobial treatment incidence (ATI; the theoretical number of animals per 1000 animal-days subjected to antimicrobial treatment) to indicate antimicrobial use on each farm. The farms in which MRS or ESBL-producing coliforms were isolated from at least one mastitic milk sample were classified as antimicrobial resistance (AMR)-positive, and those in which neither MRS nor ESBL-producing coliforms were isolated were classified as AMR-negative. The AMR-positive farms showed a significantly higher ATI (median 45.17) than AMR-negative farms (median 38.40). The results indicate that high antimicrobial usage is associated with AMR in staphylococci and coliforms isolated from mastitic milk on dairy farms in Chiba Prefecture. Abstract : Antimicrobial use; Antimicrobial resistance (AMR); Defined daily dose (DDD); Antimicrobial treatment incidence (ATI); Dairy cattle; Japan; Methicillin-resistant staphylococci (MRS); Extended-spectrum beta-lactamase (ESBL)-producing coliforms; Mastitis.